2021
DOI: 10.1039/d1sc04245a
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced C(sp3)–H sulfination empowers the direct and chemoselective introduction of the sulfonyl group

Abstract: Direct installation of the sulfinate group by a functionalization of unreactive aliphatic C–H bonds can provide an entry to most classes of organosulfur compounds, because of the central position of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…Despite the well-known importance of sulfoxides and significant advances in C–H functionalization, the conversion of C­(sp 3 )–H bonds into sulfoxides remains undeveloped. Recently, Macmillan and Larionov independently showed that C­(sp 3 )–H sulfination can be realized via a photoinduced HAT process (Scheme c) . The generated alkyl radicals could add to sulfur dioxide and further give rise to the corresponding sulfinates, which can be in situ transferred to a range of sulfonyl compounds.…”
mentioning
confidence: 99%
“…Despite the well-known importance of sulfoxides and significant advances in C–H functionalization, the conversion of C­(sp 3 )–H bonds into sulfoxides remains undeveloped. Recently, Macmillan and Larionov independently showed that C­(sp 3 )–H sulfination can be realized via a photoinduced HAT process (Scheme c) . The generated alkyl radicals could add to sulfur dioxide and further give rise to the corresponding sulfinates, which can be in situ transferred to a range of sulfonyl compounds.…”
mentioning
confidence: 99%
“…More recently, a procedure for photoinduced aliphatic C-H bond sulfination that employs sodium metabisulfite (Na 2 S 2 O 5 ) under UV-B light irradiation (l = 300 nm) was developed. 146 The reaction proceeds under mild conditions affording sulfonate products in moderate to good site-selectivity, that can be easily converted into methyl and allyl sulfones by reaction with the pertinent iodide.…”
Section: Other Functionalizationsmentioning
confidence: 99%
“…In recent years, activation of aliphatic C(sp 3 )–H bonds via hydrogen atom transfer (HAT) reaction has been demonstrated to be a powerful tool to generate carbon-centered radicals that has appeared to be a promising alternative to the traditional ones as it does not require prior functionalization of the starting materials. 13 In 2021, MacMillan 14 and Larionov 15 groups reported the stepwise approaches successively, which enabled the access to dialkyl sulfones via photoinduced direct C(sp 3 )–H sulfinylation and the following alkylation (Fig. 1D).…”
Section: Introductionmentioning
confidence: 99%